ANALISA KENAIKAN BEBAN LISTRIK SEKTOR RUMAH TANGGA TERHADAP BEBAN PUNCAK DI KOTA PALANGKA RAYA - Septiana, Gebi; Dyana Arjana, I Gede; Arta Wijaya, I Wayan (Jurnal SPEKTRUM, 2024)
Electricity is an essential need in the life of Palangka Raya City, and it can be utilized across various sectors such as business, social, industrial, governmental, and household. The increase in population growth in Palangka Raya City has led to a rise in the demand for electricity, necessitating its regulation and efficient distribution to customers. Specifically in the electricity sector, particularly in households, the demand tends to fluctuate due to resistive, inductive, and capacitive loads. This study aims to analyze the load factor, which is the ratio of average load to peak load measured over certain periods such as daily, monthly, or yearly. The first step involves data collection in the household sector of Palangka Raya City, including tariff data and monthly consumption data. The second step involves classifying electrical loads followed by an analysis of load factor accumulation. The third step involves summarizing the results of the accumulation data. From the analysis, it is concluded that the highest load factor values are found in the R.1/450 VA category, with an average of 49.30%, and the highest power factor value is 83.16% compared to other load factor categories. However, tariffs for R.3/6,600 VA and above show a gradual decrease in load factor from February to December.